Features of Rural Tourism as an Element of Kazakh Culture during the Pandemic Syndrome - TLEUBAYEVA, Aitolkyn; ZHAKUPOV, Altynbek; SHOKHAN, Roza; NURGAZINA, Aizharkyn; KARIPBAYEV, Zhanbota; SIYEUBAYEVA, Maral; DOSSOVAk, Makhabbat (Journal of Environmental Management and Tourism, 2023)
The article discusses the prospects for developing rural tourism as one of the tools for shaping the country's image during and after the pandemic period. The tourism sphere of Kazakhstan, in which there were noticeable changes during the pandemic, is analyzed. Areas infected with coronavirus infection were shown on the map. Also, separately studied the data of the tourism sector of the Akmola and Karaganda regions during the pandemic. Marketing and sociological surveys were conducted to find determine residents' opinion of holiday destinations during the pandemic. In the example of neighboring regions of Akmola and Karaganda regions, some tourist objects contributing to the formation of the image and development of rural tourism were highlighted and marked on the map. The key strengths of rural tourism development for the Republic of Kazakhstan, which can contribute to the sustainable formation of the country's image, are identified and recommended. The article compares the effects of COVID-19 and its impact on tourism development. Thus, the pandemic allows the development of domestic tourism in the country, due to which the population began to choose and give preference to tourist sites and routes within the country.